Mini-Factor H Modulates Complement-Dependent IL-6 and IL-10 Release in an Immune Cell Culture (PBMC) Model: Potential Benefits Against Cytokine Storm - Kozma, Gergely Tibor; Mészáros, Tamás; Bakos, Tamás; Hennies, Mark; Bencze, Dániel; Uzonyi, Barbara; Győrffy, Balázs; Cedrone, Edward; Dobrovolskaia, Marina A.; Józsi, Mihály; Szebeni, János (Frontiers in Immunology, 2021)
Cytokine storm (CS) is known to play a key role in the fatal outcome of COVID-19. Considering the increasing evidence that complement activation is involved in this severe immune derangement and that complement inhibitors may have clinical benefits in COVID-19, studying the effects of complement inhibitors in a CS model holds promise to identify new drugs effective against the pandemic. We used peripheral blood mononuclear cells (PBMCs) cultured in the presence of autologous serum as an in vitro model of CS and tested the impact of complement inhibition on the cytokine release by known activators of complement and/or immune cells via different pattern recognition receptors, including liposomal amphotericin (AmBisome), yeast beta-glucan (Zymosan) and bacterial lipopolysaccharide (LPS). Next, multiplex panels of cytokines and complement split products were used to assess the model’s responses to these treatments. The data revealed ~5- to ~2000-fold rise in IL-, IL-, IL-5, -6, -8, -10, -12, -13 and TNF at 6 and 18 h, with TNFreaching plateau at 6 h. These changes in cytokine response were preceded by significant rises of complement activation markers C3a, C4a, C5a, Ba, Bb and sC5b-9 at 45 min of incubation. Inhibition of complement activation by EDTA, serum heat-inactivation or mini-factor H (mini-fH) had varying suppressive effects on the release of most cytokines at 6 and 18 h. Importantly, mini-fH significantly inhibited IL-6, a cytokine commonly named as the main driver of CS in patients, and stimulated secretion of IL-10, known for its anti-inflammatory activity. These findings suggest the potential utility of mini-Factor H in mitigating the risks of CS caused by infectious agents (e.g., in bacterial sepsis and COVID-19) and some therapeutic agents (e.g., CAR-T therapies).